2023
DOI: 10.1021/acsami.3c00187
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Chemical Effects of Clays and Other Fillers in the Preparation of Epoxy–Vinyl Ether Composites Using Radical-Induced Cationic Frontal Polymerization

Abstract: Addition of fillers to formulations can generate composites with improved mechanical properties and lower the overall cost through a reduction of chemicals needed. In this study, fillers were added to resin systems consisting of epoxies and vinyl ethers that frontally polymerized through a radical-induced cationic frontal polymerization (RICFP) mechanism. Different clays, along with inert fumed silica, were added to increase the viscosity and reduce the convection, results of which did not follow many trends p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Fillers or fibers have a positive impact on the propagation of frontally polymerizable resins, which might explain the distinctive increase in the T g from neat resin to the composite. 2,52 The successful RCFP curing of high thickness CFRC showed that it is possible to cure such components under low oven heating and at a much shorter curing duration than conventional anhydride cured resins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fillers or fibers have a positive impact on the propagation of frontally polymerizable resins, which might explain the distinctive increase in the T g from neat resin to the composite. 2,52 The successful RCFP curing of high thickness CFRC showed that it is possible to cure such components under low oven heating and at a much shorter curing duration than conventional anhydride cured resins.…”
Section: Resultsmentioning
confidence: 99%
“…Radical induced cationic frontal polymerization (RICFP) has gained a lot of attention amongst researchers in the past few years, as a rapid curing substitute for various cyclic ether monomers. 1–7 The well-known cationic frontal polymerization involves generation of radicals and cations when diaryliodonium salts are photo or thermal cleaved, when subjected to ultraviolet light or heat. A strong Brønsted acid is produced that protonates cyclic ether monomers forming highly reactive cations that are able to react with adjacent cyclic ether groups forming polyether in a ring opening cationic polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to the differences in structure of the TEGDVE versus BADGE, where the former is a structurally linear monomer with ether linkages that facilitate bending compared to the aromatic rings of BADGE, which provide rigidity. Polymers containing TEGDVE with epoxy and produced with RICFP have been previously reported to be flexible. , To maintain reactivity but improve the rigidity of the polymer, CE was added, which contains two cyclohexane rings for increased rigidity unlike TEGDVE. The final resin composition of 3:1:1 BADGE:CE:TEGDVE (wt:wt:wt) with 1 phr IOC-8 and 1 phr Luperox 231 was chosen as the optimal balance of reactivity and physical properties while supporting a front at the printing diameter to allow for the front-driven printing.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The effects of resin composition, initiator concentration, filler type, and loading on front kinetics were investigated. Carbon nanofibers (CNFs) and milled carbon fibers (MCFs) were compared as fillers to tune front kinetics, and CNFs were investigated to manipulate mechanical properties, while fumed silica (FS) was used to further tailor viscosity, as FS is inert in RICFP. , CNFs are smaller than carbon fibers and have a higher specific surface area, which could assist in improving physical properties. They are larger than CNTs, less thermally conductive, and differ in their physical structure, being cylinders composed of stacked layers versus hollow CNTs; , CNFs have the advantage of being less expensive than CNTs while still possessing beneficial thermal properties for FP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation